Glass plate concave-flexible armored super-hydrophobic microstructure and preparation method thereof
Through femtosecond laser etching and chemical fluorination technology, the construction of equally distributed grooved superhydrophobic microstructures on glass plates has solved the shortcomings of the existing glass superhydrophobic surface in terms of durability and light transmittance, and achieved low cost , efficient superhydrophobic performance improvement, suitable for a variety of glass applications.
Patent Information
- Application Number
- CN202411345319.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
The existing glass superhydrophobic surface structure has shortcomings in terms of durability and light transmittance. The traditional methods are costly, complex in processes and are susceptible to environmental factors, resulting in performance degradation.
Femtosecond laser etching and chemical fluorination technology are used to construct an equally distributed grooved superhydrophobic microstructure on glass plates. The microstructure characteristic parameters are designed based on the Cassie-Baxter infiltration model, and low surface energy is formed through ultrasonic cleaning and fluorination treatment. and flexible armor to improve impact resistance.
It realizes low-cost and controllable superhydrophobic microstructure preparation of glass plates, improves durability and light transmittance, and is suitable for construction, automobile and photovoltaic glass fields.
Smart Images

Figure CN119191718A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of glass plate surface structure design and preparation, and in particular relates to a method for constructing a super-hydrophobic microstructure of grooves with equal spacing distribution and a preparation method for forming a flexible armor by femtosecond laser etching and chemical fluorination. Background Art
[0002] With the rapid development of nanotechnology and surface engineering technology, scientists have successfully prepared materials with super-hydrophobic properties by changing the microstructure of the material surface; by coating or constructing micro-nano structures on its surface, extreme water repellency is achieved, thus showing excellent waterproof, anti-fouling, self-cleaning and other properties. In the field of architecture, super-hydrophobic glass is widely used in windows, curtain walls, etc. Its waterproof and anti-fog properties can effectively improve the visual effect and service life of the building. The photovoltaic industry is developing rapidly today. The dust deposition on the surface of photovoltaic glass panels makes the transmittance worse, resulting in reduced photoelectric efficiency conversion. The traditional way of cleaning dust has high labor costs, consumes water resources, and also causes problems such as damage to the surface of the glass panel. Therefore, it is necessary to prepare super-hydrophobic function on the glass surface. In the past few decades, researchers have prepared super-hydrophobic surfaces through various methods, among which the design and preparation of micro-nano surfaces is one of the important ways. However, traditional super-hydrophobic glass panels are usually achieved by chemical coating or surface treatment. However, these methods have problems such as easy detachment of the coating and environmental pollution, and the processing process is complicated and the cost is high. Therefore, finding a simple, efficient and controllable preparation method has become the current research focus.
[0003] Superhydrophobic surface refers to the micro-nanostructure surface with a contact angle of water droplets greater than 150° and a rolling angle less than 10° on the material surface. The superhydrophobicity of the material surface has excellent properties such as waterproof, self-cleaning, anti-icing, drag reduction, and anti-corrosion, which makes the superhydrophobic surface have broad application prospects in many fields, such as biomedicine, liquid transportation, clothing and textile fields, construction fields, transportation vehicles, aerospace fields, etc. It is an important direction for energy conservation and environmental protection under the current scientific and technological progress. Its excellent characteristics include but are not limited to automatic cleaning ability, resistance to dust and oil adhesion, excellent high light transmittance and corrosion resistance, and prevention of ice and frost coverage. As the research focus in the field of surface science and engineering technology, superhydrophobic surface, with its unique properties of high contact angle and low contact angle hysteresis, provides strong support for the realization of waterproof treatment, self-cleaning technology and the development of anti-fog function, indicating a broad prospect in future applications.
[0004] Based on the principle of superhydrophobic surface design and preparation, the inventor of this patent application has carried out research on superhydrophobic surface design with the support of the Hebei Provincial Natural Science Foundation General Project (Research on the superhydrophobic mechanism of the slip zone of Nepenthes and the bionic preparation technology of micro-nano composite structure, E2019208306), the Central Guidance Local Science and Technology Development Fund Project (Research on femtosecond laser preparation technology of superhydrophobic micro-nano composite structure on titanium alloy surface, 226Z1804G) and other projects. The micro-morphological structure of the slip zone of Nepenthes that can present superhydrophobic properties was used as the bionic prototype, and a superhydrophobic surface was designed and prepared using 3D printing technology and high-voltage electrostatic adsorption technology. The test results show that the water drop contact angle of the prepared superhydrophobic surface is 152.6°, indicating that it has good superhydrophobic function (authorized invention patent, patent number ZL 202010458218.7; academic paper, Bioinspired, Biomimetic and Nanobiomaterials, 2022, 11(1): 1-7). Therefore, the patent applicant has the basic conditions for designing and preparing super-hydrophobic surfaces.
[0005] Invention patent 2021101175202.2 discloses a super-hydrophobic self-cleaning material for solar photovoltaic glass and its preparation method. The surface is prepared by chemical modification and composite materials, so that the surface of photovoltaic glass has super-hydrophobicity and self-cleaning function. However, the chemical materials used in this patent are expensive, the production process is complicated, and the time-consuming cost is long-term exposure to outdoor environments. It is affected by factors such as ultraviolet rays, temperature, and humidity changes, resulting in material performance degradation or failure. In areas with strong winds and sand, the surface of the material is easily worn, thereby affecting the self-cleaning effect. Invention patent 202111190808.7 discloses a method for preparing a super-hydrophobic functional surface of optical glass by hot pressing. An ultrafast laser is used to process a microstructure with micro-nano particles on the surface of a cemented carbide material, and the processed mold is modified with low surface energy to obtain a microstructure mold with super-hydrophobic properties. However, the processing cost of this patent is high, which will increase the difficulty and cost of the mold. The process parameters such as temperature, pressure, and time in the hot pressing process have a significant impact on the performance of the final product and need to be precisely controlled. If the process parameters are not properly controlled, it may lead to unstable product quality or performance degradation.
[0006] In summary, in the field of design and preparation of super-hydrophobic structures for glass plates, the existing super-hydrophobic surface structure designs of glass are still lacking in durability and light transmittance. Therefore, the present invention provides a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method, constructs grooves with equal spacing, and completes the processing of the microstructure by etching the surface of the glass plate by femtosecond laser, and reduces the surface energy by chemical fluorination, thereby realizing the preparation of a low-surface-energy super-hydrophobic microstructure. The present invention provides a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method, which provides a new design method and low-cost preparation method for the surface of a low-surface-energy glass plate, and can be widely used in the fields of architectural glass, automotive glass, electronic screens, photovoltaic glass, etc., and has important application value. Summary of the invention
[0007] The present invention provides a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method thereof, designs grooves with equal spacing, derives and establishes a numerical equation between super-hydrophobic microstructure characteristics and super-hydrophobic function, i.e., contact angle, based on the Cassie-Baxter wetting model, clarifies the microstructure characteristic parameters corresponding to the contact angle greater than 150°, simulates the contact angle of a droplet on the super-hydrophobic microstructure of a glass plate and the transmittance of light when irradiating the super-hydrophobic microstructure of a glass plate, and completes the design of the super-hydrophobic microstructure; the glass plate is ultrasonically cleaned and dried, and the treated glass plate is subjected to femtosecond laser etching to prepare grooves with micron-level structural parameters and equal spacing; in order to improve the super-hydrophobic properties of the grooves of the glass plate prepared by femtosecond laser, the grooves are subjected to fluorination treatment to obtain a glass plate super-hydrophobic microstructure with low surface energy; and the fluorinated film formed after chemical fluorination can act as a flexible armor to enhance the impact resistance of the super-hydrophobic microstructure, thereby improving durability. The technical scheme adopted by the present invention is: A glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method thereof, characterized by comprising the following steps: Step 1, designing a super-hydrophobic surface microstructure, which is composed of grooves distributed at equal intervals; Step 2, based on the Cassie-Baxter wetting model of superhydrophobic theory, a numerical equation between equally spaced grooves and the superhydrophobic function, i.e., the contact angle of a water droplet, is derived and established. The numerical equation is: , Where: i T and i c They represent the theoretical value of contact angle and the intrinsic contact angle, respectively. The intrinsic contact angle of the glass plate after chemical fluorination is 103°; R、H、L They are respectively the radius of the semicircle at the bottom of the groove, the depth of the groove, and the interval between the grooves; l is the wetting coefficient, that is, the degree of wetting of the groove by the water droplet. When the water droplet floats on the top of the groove l=0, when the water droplet completely wets the groove l =1; The numerical equation is used to determine the microstructure characteristic parameters corresponding to a water drop contact angle greater than 150°, and the microstructure design of the super-hydrophobic glass plate is completed; Step 3, using ANSYS software to simulate the contact angle of the super-hydrophobic microstructure of the glass plate, simulating the contact angle generated when a water droplet with a volume of 2 to 8 μL falls on the surface of the super-hydrophobic microstructure of the glass plate; Step 4, using LighTools software to simulate the transmittance of the super-hydrophobic microstructure of the glass plate, setting the incident angle of the light to 80°~90°, and simulating the refraction, reflection, and transmission of the light; Step 5, the glass plate is ultrasonically cleaned in anhydrous ethanol for 10-15 minutes, and the temperature is kept at 50-60° C. for 30-40 minutes, and the surface of the cleaned glass plate is processed by femtosecond laser to prepare grooves with equal spacing; Step 6, in order to improve the super-hydrophobic properties of the glass plate after femtosecond laser processing, it is chemically fluorinated to reduce the surface energy of the glass plate. At the same time, the fluorinated film layer formed after chemical fluorination can act as a flexible armor, enhance the impact resistance of the super-hydrophobic microstructure, and thus improve the durability; the glass plate after femtosecond laser etching is placed in a beaker and deionized water is added, and it is placed in an ultrasonic cleaning machine for cleaning for 50-60 minutes, and the temperature is kept at 50-60°C for 30-40 minutes, and the dried glass plate super-hydrophobic microstructure is placed in a mixture of 2% to 4% by mass of heptadecafluorosilane in anhydrous ethanol, and immersed at 60-70°C for 120-130 minutes; the glass plate after chemical fluorination treatment is placed in a drying oven at 120-130°C, and is dried at a constant temperature for 60-70 minutes, thereby preparing a super-hydrophobic surface of the glass plate.
[0008] Step 1 specifically includes: (1) Designing equally spaced grooves as superhydrophobic microstructures, with the grooves and glass plate forming an integrated structure; (2) When light shines on the super-hydrophobic microstructure of the glass plate, the evenly spaced groove structure can cause the light to be reflected multiple times in the grooves, thereby focusing light and improving light transmittance; (3) The grooves can effectively retain air, forming an air film layer, reducing the contact area between the droplets and the superhydrophobic microstructure, and producing a larger contact angle, thereby achieving the superhydrophobic function.
[0009] Step 2 specifically includes: (1) The designed groove has micrometer-scale structural characteristic parameters, where the radius of the semicircle at the bottom of the groove is R Designed to be 18~22μm, depth H Designed to be 46~54μm, the groove pitch L Designed to be 36~40μm; (2) The characteristic parameters of the superhydrophobic microstructure with equally spaced grooves are substituted into the numerical equation to calculate the theoretical value of the water droplet contact angle. The superhydrophobic function is determined based on whether the contact angle is greater than 150°. This enables the controllable design of the superhydrophobic surface and clarifies the characteristic parameters of the superhydrophobic microstructure.
[0010] Step 3 specifically includes: (1) Import the model with clear characteristic parameters of the super-hydrophobic microstructure of the glass plate into ANSYS software to simulate the morphology of water droplets on the super-hydrophobic microstructure of the glass plate; (2) The process of simulating a water droplet with a volume of 2 to 8 μL infiltrating the super-hydrophobic microstructure of a glass plate was simulated, and the contact angle of the water droplet was measured to be 150.17°~151.29°.
[0011] Step 4 specifically includes: (1) Import the model with clear superhydrophobic microstructure characteristic parameters into the LighTools software and set the incident angle of the light to 80°~90°; (2) Simulate the refraction, reflection, and transmission of light, and the simulated transmittance is 86.1%~90.3%.
[0012] Step 5 specifically includes: (1) Select a glass plate as the base material of the superhydrophobic microstructure and cut it into a glass plate with a length × width of 3 cm × 3 cm; (2) The glass plate is ultrasonically cleaned in anhydrous ethanol for 10 to 15 minutes, and then dried at a constant temperature of 50 to 60°C for 30 to 40 minutes to dry the cleaned glass plate; (3) placing the dried glass plate on the three-dimensional motion platform of the femtosecond laser system, adjusting the laser focus to the surface of the glass plate, and determining the laser scanning path according to the characteristic parameters of the super-hydrophobic microstructure determined in step 2; (4) Set the femtosecond laser processing parameters: average power 20 W, spot radius 3 μm, pulse width 800 fs, laser frequency 400 kHz; (5) The processing of super-hydrophobic microstructures with evenly spaced grooves can be completed simply by etching the surface of the glass plate with a femtosecond laser.
[0013] Step 6 specifically includes: (1) In order to improve the super-hydrophobic properties of the glass plate after femtosecond laser processing, chemical fluorination treatment is performed to reduce the surface energy of the glass plate. At the same time, the fluorinated film layer formed after chemical fluorination can act as a flexible armor to enhance the impact resistance of the super-hydrophobic microstructure, thereby improving durability; the glass plate after femtosecond laser etching is placed in a beaker, and a 2% to 4% by mass fluorosilane anhydrous ethanol solution is added. At room temperature, the beaker is placed in a magnetic stirrer and vigorously stirred for 60 to 70 minutes, and then the above glass plate is immersed in the mixed solution of fluorosilane anhydrous ethanol at 60 to 70°C for 120 to 130 minutes; (2) The glass plate after chemical fluorination treatment is placed in a drying oven at 120-130°C and dried at a constant temperature for 60-70 minutes to prepare a super-hydrophobic microstructure of the glass plate.
[0014] The present invention discloses a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method thereof. Grooves with equal spacing are designed. Based on the Cassie-Baxter wetting model, a numerical equation is derived and established to clarify the characteristic parameters of the microstructure, so as to realize the controllable design of the super-hydrophobic microstructure. The advantages of high precision, controllability, flexibility and high efficiency of femtosecond laser are fully utilized to complete the processing of grooves with equal spacing on the glass plate. A fluorosilane anhydrous ethanol solution with a mass ratio of 2% to 4% is used to perform fluorination treatment on the glass plate, so as to obtain a glass plate super-hydrophobic microstructure with low surface energy. The super-hydrophobic microstructure has important application value in the fields of photovoltaic cell glass surface, automobile windshield and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The overall structural diagram of the present invention; Figure 2 A schematic cross-sectional view of the groove structure of the present invention; Figure 3 A schematic diagram of light reflection of the present invention; Figure 4 A schematic diagram of a simulation of the contact angle of a glass plate of the present invention; Figure 5 Simulation diagram of light irradiating a glass plate according to the present invention; Figure 6 Schematic diagram of the cleaning, femtosecond laser processing, scanning path and fluorination treatment of the present invention; Figure 7 A physical picture of the glass plate of the present invention after processing; Figure 8 Design flow chart of the present invention.
[0016] In the figure: 1-glass plate, 2-groove, 3-semicircular reflection groove. DETAILED DESCRIPTION
[0017] The following is a detailed description of a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method of the present invention in conjunction with the embodiments and drawings.
[0018] The present invention discloses a concave-flexible armor-type super-hydrophobic microstructure of a glass plate and a preparation method thereof. Equally spaced grooves are designed, and based on the Cassie-Baxter wetting model, the numerical relationship between the equally spaced grooves and the super-hydrophobic function, i.e., the contact angle, is derived and established; the characteristic parameters of the equally spaced grooves corresponding to the contact angle being greater than 150° are clearly calculated. The glass plate is ultrasonically cleaned and dried, and the treated glass plate is subjected to femtosecond laser etching to prepare grooves with micron-level structural parameters and equal spacing; in order to improve the super-hydrophobic properties of the grooves of the glass plate prepared by femtosecond laser, the grooves are subjected to fluorination treatment to obtain a glass plate super-hydrophobic microstructure with low surface energy.
[0019] The present invention provides a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method thereof, which specifically comprises the following steps: 1. Design a super-hydrophobic surface microstructure, which consists of a microstructure of grooves distributed at equal intervals, including: (1) Designing a super-hydrophobic microstructure with grooves distributed at equal intervals, with the grooves and glass plate forming an integrated structure; (2) When light is irradiated on the super-hydrophobic microstructure, the equally spaced grooves on the super-hydrophobic microstructure can cause the light to be reflected multiple times in the grooves, thereby focusing light and improving the transmittance; (3) The grooves can effectively retain air and form an air film layer, which reduces the contact area between the droplets and the superhydrophobic microstructure, produces a larger contact angle, and realizes the superhydrophobic function.
[0020] 2. Based on the Cassie-Baxter wetting model of superhydrophobic theory, derive and establish the numerical equation between equally spaced grooves and the superhydrophobic function, i.e., the water drop contact angle, clarify the microstructure characteristic parameters corresponding to the water drop contact angle greater than 150°, and complete the superhydrophobic microstructure design, including: (1) The designed groove has micrometer-scale structural characteristic parameters, where the radius of the semicircle at the bottom of the groove is R Designed to be 18~22μm, depth H Designed to be 46~54μm, the groove pitch L Designed to be 36~40μm; (2) Based on the Cassie-Baxter wetting model, a numerical equation is derived to establish the relationship between the structural characteristics of the equally spaced grooves and the superhydrophobic function, i.e., the contact angle of the water droplet. The Cassie-Baxter wetting model assumes that when a liquid droplet infiltrates a solid surface, air can be retained in the microstructure of the solid surface. Therefore, the contact surface consists of three parts: the liquid droplet, the air, and the solid surface microstructure. Based on this, the Cassie-Baxter equation is proposed: (1), In the formula, i T is the contact angle, i c is the intrinsic contact angle, f s1 is the ratio of the actual wetted solid area of the droplet to the apparent geometric contact area. f r Indicates the roughness coefficient, that is, the non-smoothness of the surface. Figure 1 , Figure 2 As shown in the figure, the designed super-hydrophobic microstructure is composed of grooves with equal spacing, and the projected area of the unit microstructure is S P It can be calculated by formula (2): (2), The actual surface area S generated by the unit microstructure S It is composed of grooves and groove intervals and is calculated using the following formula: (3), In the formula, R is the radius of the semicircle at the bottom of the groove, H is the depth of the groove, L is the spacing of the grooves; (4), When water droplets infiltrate the designed groove super-hydrophobic microstructure, the grooves will be infiltrated to different degrees, so the wetting coefficient is introduced l ; At this time, the water droplet infiltrates the groove of the glass plate, so the ratio of the actual groove area of the water droplet to the apparent geometric contact area is f s1 It can be obtained by formula (5): (5), Where: f s1 It represents the ratio of the actual wetted solid area of the droplet to the apparent geometric contact area; l represents the wetting coefficient; Substituting formula (4) and formula (5) into formula (1), the numerical relationship between the designed micro-nano composite structure characteristics and the superhydrophobic function, i.e., the water drop contact angle, can be obtained as follows: (6), Where: i T and i c They represent the theoretical contact angle and the intrinsic contact angle, respectively. The intrinsic contact angle of a water drop on a glass plate ic is 103°; (3) Substitute the structural characteristic parameters of the equally spaced grooves into the numerical equation, calculate the theoretical value of the water drop contact angle, and determine whether it has a super-hydrophobic function based on whether the contact angle is greater than 150°, and clarify the characteristic parameters of the super-hydrophobic microstructure. In the embodiment, the characteristic parameters are set as: the radius of the semicircle at the bottom of the groove R Designed to 20μm, depth H Designed to be 50μm, the groove pitch L Designed to be 38μm, the wetting coefficient is l =0.2. Substitute the above parameters into formula (6) to calculate the contact angle of the designed super-hydrophobic surface i T =150.73°, indicating good superhydrophobic function.
[0021] 3. Use ANSYS software to simulate the contact angle of the super-hydrophobic microstructure of the glass plate. Specifically include: (1) Import the model with clear characteristic parameters of the super-hydrophobic microstructure of the glass plate into ANSYS software to simulate the morphology of water droplets on the super-hydrophobic microstructure of the glass plate; (2) The process of 5 μL water droplet infiltrating the super-hydrophobic microstructure of the glass plate was simulated, and the contact angle of the water droplet was measured to be 150.73°.
[0022] 4. Use LighTools software to simulate the transmittance of the super-hydrophobic microstructure of the glass plate. Specifically include: (1) Import the model with clear superhydrophobic microstructure characteristic parameters into the LighTools software and set the angle of the incident light to 85°; (2) Simulating the refraction, reflection, and transmission of light, the simulation shows that the transmittance of the glass plate is 88.6%.
[0023] 5. The glass plate is ultrasonically cleaned in anhydrous ethanol and dried, and the surface of the cleaned glass plate is etched by femtosecond laser to prepare grooves with equal spacing. Specifically including: (1) Select a glass plate as the super-hydrophobic microstructure substrate material and cut it into a glass plate with a length × width of 3 cm × 3 cm; (2) The glass plate was ultrasonically cleaned in anhydrous ethanol for 13 min and kept at a constant temperature of 55°C for 35 min to dry the cleaned glass plate; (3) placing the dried glass plate on the three-dimensional motion platform of the femtosecond laser system, adjusting the laser focus to the surface of the glass plate, and determining the laser scanning path according to the characteristic parameters of the super-hydrophobic microstructure determined in step 2; (4) Set the femtosecond laser processing parameters: average power 20 W, beam radius 3 μm, pulse width 800 fs, laser frequency 400 kHz; (5) The processing of evenly spaced grooves, i.e., super-hydrophobic microstructures, can be completed simply by etching the surface of the glass plate with a femtosecond laser.
[0024] 6. In order to improve the super-hydrophobic properties of the glass plate after femtosecond laser processing, chemical fluorination treatment is performed to reduce the surface energy of the glass plate. At the same time, the fluorinated film layer formed after chemical fluorination can act as a flexible armor to enhance the impact resistance of the super-hydrophobic microstructure, thereby improving durability. The specific steps include: (1) In order to improve the super-hydrophobic properties of the glass plate after femtosecond laser processing, it was subjected to chemical fluorination treatment to reduce the surface energy of the glass plate. At the same time, the fluorinated film layer formed after chemical fluorination can act as a flexible armor, enhancing the impact resistance of the super-hydrophobic microstructure, thereby improving the durability; the glass plate after femtosecond laser etching was placed in a beaker and added with deionized water, and then placed in an ultrasonic cleaning machine for cleaning for 55 minutes, and kept at a constant temperature of 55°C for 35 minutes. The dried glass plate super-hydrophobic microstructure was placed in a mixture of 2% by mass of heptafluorosilane in anhydrous ethanol and immersed at 65°C for 125 minutes; (2) The glass plate after chemical fluorination treatment was placed in a drying oven at 125°C and dried at a constant temperature for 65 minutes to prepare a super hydrophobic surface of the glass plate.
[0025] In summary, the present invention provides a glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method, which provides a new design method for the glass plate super-hydrophobic microstructure and can be widely used in photovoltaic glass, automotive glass, architectural glass and other fields.
Claims
1. A glass plate concave-flexible armor-type super-hydrophobic microstructure and a preparation method, characterized in that The design steps include: Step 1, designing a super-hydrophobic surface microstructure, which is composed of grooves distributed at equal intervals; Step 2, based on the Cassie-Baxter wetting model of superhydrophobic theory, a numerical equation between equally spaced grooves and the superhydrophobic function, i.e., the contact angle of a water droplet, is derived and established. The numerical equation is: , Where: θ T and θ c They represent the theoretical value of contact angle and the intrinsic contact angle, respectively. The intrinsic contact angle of the glass plate after chemical fluorination is 103°; R, H, L They are respectively the radius of the semicircle at the bottom of the groove, the depth of the groove, and the spacing of the grooves; λ is the wetting coefficient, that is, the degree of wetting of the groove by the water droplet. When the water droplet floats on the top of the groove λ =0, when the water droplet completely wets the groove λ =1; The numerical equation is used to determine the microstructure characteristic parameters corresponding to a water drop contact angle greater than 150°, and the design of the super-hydrophobic microstructure of the glass plate is completed; Step 3, using ANSYS software to simulate the contact angle of the super-hydrophobic microstructure of the glass plate, simulating the contact angle generated when a water droplet with a volume of 2 to 8 μL falls on the surface of the super-hydrophobic microstructure of the glass plate; Step 4, using LighTools software to simulate the transmittance of the super-hydrophobic microstructure of the glass plate, setting the incident angle of the light to 80°~90°, and simulating the refraction, reflection, and transmission of the light; Step 5, the glass plate is ultrasonically cleaned in anhydrous ethanol for 10-15 minutes, and the temperature is kept at 50-60° C. for 30-40 minutes, and the surface of the cleaned glass plate is processed by femtosecond laser to prepare grooves with equal spacing; Step 6: In order to improve the super-hydrophobic properties of the glass plate after femtosecond laser processing, it is subjected to chemical fluorination treatment to reduce the surface energy of the glass plate. At the same time, the fluorinated film layer formed after chemical fluorination can act as a flexible armor to enhance the impact resistance of the super-hydrophobic microstructure, thereby improving durability.
2. A glass plate concave-flexible armor-type super-hydrophobic microstructure and preparation method according to claim 1, characterized in that: Step 1 specifically includes: (1) Designing equally spaced grooves as superhydrophobic microstructures, with the grooves and glass plate forming an integrated structure; (2) When light shines on the super-hydrophobic microstructure of the glass plate, the evenly spaced groove structure can cause the light to be reflected multiple times in the grooves, thereby focusing light and improving light transmittance; (3) The grooves can effectively retain air, forming an air film layer, reducing the contact area between the droplets and the superhydrophobic microstructure, and producing a larger contact angle, thus achieving the superhydrophobic function.
3. A glass plate concave-flexible armor-type super-hydrophobic microstructure and preparation method according to claim 1, characterized in that: Step 2 specifically includes: (1) The designed groove has micrometer-scale structural characteristic parameters, where the radius of the semicircle at the bottom of the groove is R Designed to be 18~22μm, depth H Designed to be 46~54μm, the groove pitch L Designed to be 36~40μm; (2) The characteristic parameters of the superhydrophobic microstructure with equally spaced grooves are substituted into the numerical equation to calculate the theoretical value of the water droplet contact angle. The superhydrophobic function is determined based on whether the contact angle is greater than 150°. This enables the controllable design of the superhydrophobic surface and clarifies the characteristic parameters of the superhydrophobic microstructure.
4. A glass plate concave-flexible armor-type super-hydrophobic microstructure and preparation method according to claim 1, characterized in that: Step 3 specifically includes: (1) Import the model with clear characteristic parameters of the super-hydrophobic microstructure of the glass plate into ANSYS software to simulate the morphology of water droplets on the super-hydrophobic microstructure of the glass plate; (2) The process of 2-8 μL water droplets infiltrating the super-hydrophobic microstructure of a glass plate was simulated, and the contact angle of the water droplets was measured to be 150.17°~151.29°.
5. The glass plate concave-flexible armor-type super-hydrophobic microstructure and preparation method according to claim 1, characterized in that: Step 4 specifically includes: (1) The model with clear characteristic parameters of superhydrophobic microstructure was imported into LighTools software, and the angle of incident light was set to 80°~90°; (2) Simulate the refraction, reflection, and transmission of light, with the simulated transmittance ranging from 86.1% to 90.3%.
6. The glass plate concave-flexible armor-type super-hydrophobic microstructure and preparation method according to claim 1, characterized in that: Step 5 specifically includes: (1) Select a glass plate as the base material of the superhydrophobic microstructure and cut it into a glass plate with a length × width of 3 cm × 3 cm; (2) The glass plate is ultrasonically cleaned in anhydrous ethanol for 10-15 minutes and kept at a constant temperature of 50-60°C for 30-40 minutes to dry the cleaned glass plate; (3) placing the dried glass plate on the three-dimensional motion platform of the femtosecond laser system, adjusting the laser focus to the surface of the glass plate, and determining the laser scanning path according to the characteristic parameters of the super-hydrophobic microstructure determined in step 2; (4) Set the femtosecond laser processing parameters: average power 20 W, spot radius 3 μm, pulse width 800 fs, laser frequency 400 kHz; (5) The processing of evenly spaced grooves, i.e., super-hydrophobic microstructures, can be completed simply by etching the surface of the glass plate with a femtosecond laser.
7. The glass plate concave-flexible armor-type super-hydrophobic microstructure and preparation method according to claim 1, characterized in that: Step 6 specifically includes: (1) In order to improve the super-hydrophobic properties of the glass plate after femtosecond laser processing, chemical fluorination treatment was performed to reduce the surface energy of the glass plate. The glass plate after femtosecond laser etching was placed in a beaker and deionized water was added. It was placed in an ultrasonic cleaning machine for cleaning for 50-60 minutes and kept at a constant temperature of 50-60°C for 30-40 minutes. The dried glass plate super-hydrophobic microstructure was placed in a mixture of 2%-4% by mass of heptadecafluorosilane in anhydrous ethanol and immersed at 60-70°C for 120-130 minutes. (2) The glass plate after chemical fluorination treatment is placed in a drying oven at 120-130°C and dried at a constant temperature for 60-70 minutes to prepare a super hydrophobic surface of the glass plate.
